Cybercrime and law: Managing challenges and prospects in the digital age - Marković, M.Darko; Marković, Darija (Pravo, teorija i praksa, 2025)
Cybercrime has emerged as a global threat in the digital age, posing significant challenges to legal systems worldwide, particularly in terms of their effectiveness and applicability. This paper examines how these challenges are addressed within international and national legal frameworks, highlighting key obstacles and offering perspectives for improvement. It reviews existing legal mechanisms, such as the Budapest Convention, the General Data Protection Regulation (GDPR), and national legislation in Serbia, and evaluates their adaptability to contemporary technological threats and potential for reform. The research adopts an interdisciplinary methodology, combining theoretical analysis of international and domestic legal texts with empirical examination of statistical data and case records. Practical challenges of legal enforcement are assessed through a systematic review of relevant sources, including the number of reported cyberattacks, and insights drawn from Interpol and Europol reports. The findings highlight systemic challenges, such as jurisdictional limitations, ineffective laws, and insufficient technical capacities. Proposed solutions emphasize enhanced international cooperation, modernization of legal frameworks, investment in technology, and public education. The paper concludes that building legal resilience to cybercrime requires a coordinated international effort to address legal and technological vulnerabilities exploited by cybercriminals.